Applicability Condition of Surface Miner at Open Cast Mine - A Case Study: Minimizing Environmental Impact and Maximizing Coal Quality with Surface Mining (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In open cast coal mining, various activities were done or being carried out only byconventional system of mining which includes drilling, blasting and crushing. All these operationsresulting a lot of adversative impacts on the environment and the surrounding atmosphere. The adverseimpacts that the conventional mining system results are ground vibration, noise pollution, air pollution,land degradation, ecological disturbances etc.This generates necessity of additional machineries and manpower, eventually cost of mining coal rises.And also due to existence of villages adjacent the mines, blasting is limited as a result massive quantityof coal is blocked. And we all know that quality of coal has great concern in our country since most ofthe coal seams comprise low-grade quality of coal due to drift origin. Government legislation alsoforbids the dispatch of coal for more than 1000 KM, if coal comprises more than 36 ash.In these circumstances, surface miner was being introduced which can proficient of solving the abovedeclared problems. This allows the operator of the mine to ensure selective mining of coal so that qualityof coal develops. The variety of thinner seams which are unworkable in conventional system of opencastmining, now converts workable and the whole reserve of non-renewable source of fossil fuel rises. It alsodecreases cost of production so that total profit of a mine growths.